Investigating the knowledge sharing activities among postgraduates students using social media tools - Hamid, Sawsan Ali (2015)
Knowledge sharing is a process where individuals mutually exchange their knowledge and jointly create new knowledge. Recently, it is found that besides face-to-face interactions, students also share their knowledge through social media tools. Social media is considered as the key value in the campus to facilitate knowledge sharing and the main tasks in order to support the daily communication. Many dimensions of knowledge sharing in social media environments have not yet been examined. Also many questions are still unanswered and need to be explored across different social media tools. Thus, this research aims to explore the knowledge sharing activities among local and international postgraduate students at Universiti Utara Malaysia (UUM) as well as find the benefits and barriers through using social media tools during sharing knowledge. Data were collected through qualitative approach. A total of 12 postgraduate students were interviewed and received answers from them through semistructure interview. Interpretive analysis method was used to find the themes by using Nvivo software. The results for this study included four sections based on Nonaka and Takeuchi theory, in the socialization section the findings show the activities for students include exchange experience and perspective as well as confirmed the important of social media in overcome time, geographical distance and cost that is a barriers to share knowledge as well as provide more confident to share ideas for students. As well as, some barriers that still issues to sharing knowledge such as lack of math-symbol and culture. In externalization section, the findings show the design the diagram and document the files as activities as well as show the important of using social media in documentation to save the files and diagram online as well as enhance English language and protect from viruses. While the barriers include uploading limitation. In combination section the findings show the modification and reflection as activities among group member and show the benefit of social media during combine the work for assignment and project is easy to use and saving paper cost. While, the barriers is downloading limitation. In internalization section the findings show the review and reflection as activities among student. The benefits include create new idea and acquiring in depth understanding while lack of personal interaction and late in answering as barriers to share knowledge. This study contributed by using the Nonaka and Takeuchi model with higher educational institutions. In the same context, there is few empirical studies focused on the IT with share knowledge, therefore this research sought to add information into the literature by shed light the barriers and the benefits through utilize the new technologies for share know among the team work